47. Early sensory and autonomic involvement in drug-naive Parkinson. Issue 12 (December 2016) - Nolano, M.; Provitera, V.; Stancanelli, A.; Caporaso, G.; Saltalamacchia, A.M.; Califano, F.; Lanzillo, B.; Iodice, R.; Manganelli, F.; Barone, P.; Santoro, L.
Abstract : Small fiber pathology has been demonstrated in Parkinson Disease (PD). To verify if it is among the early non-motor features of PD, unrelated to Levodopa therapy, we assessed function and morphology of cutaneous sensory and autonomic nerves in 32 consecutive drug-naive PD patients (M/F = 16/16; age 57.3 ± 11.1 years) and 64 age and sex matched controls. Fifty-micron-thick sections of skin samples from thigh, leg and fingertip were processed by indirect immunofluorescence techniques. Digital images were acquired using a non-laser confocal microscope. Density of intrapapillar myelinated endings (IME), Meissner's corpuscles (MC) and epidermal nerve fibers (ENFs) was calculated. Sudomotor, pilomotor and vasomotor nerves were assessed semi-quantitatively. Further evaluation included sural nerve conduction study, sympathetic skin response, quantitative sensory testing and dynamic sweat test. Nerve conduction was normal in all patients. Morphological analysis showed: a significant loss ( p < 0.01) of ENF compared to controls in all sites, a significant loss ( p < 0.01) of MC and IME in glabrous skin, a reduction of autonomic nerves involving noradrenergic and cholinergic populations. Functional assessment revealed an increase of sensory thresholds ( p < 0.01) and a reduction of sweat output ( p < 0.01). Our findings demonstrated that cutaneous denervation underlying sensory and autonomic dysfunction is an early feature in PD unrelated to Levodopa treatment.